Evaluation of the diagnostic performance of an immunoblot for ANCA and anti-GBM antibody detection - Matthias H. Busch; Joop P. Aendekerk; Joyce J. B. C. van Beers; Pieter van Paassen; Jan G. M. C. Damoiseaux (Taylor & Francis Group, 2021)
The use of high-quality antigen-specific immunoassays for detecting anti-neutrophil cytoplasmic antibodies (ANCA) and anti-glomerular basement membrane (GBM) autoantibodies is recommended in patients with suspected ANCA vasculitis and/or anti-GBM disease. We analysed the diagnostic performance of a semi-quantitative and rapid immunoblot (EUROIMMUN AG, Lübeck, Germany) in two settings. Patient sera from different cohorts (ANCA vasculitis n = 187, anti-GBM disease n = 19, and disease controls n = 51) were used. The diagnostic performance of the immunoblot was assessed when used as a confirmatory test for the presence of ANCA in suspected ANCA vasculitis and when evaluating the presence of ANCA and/or anti-GBM antibodies in AAV and/or anti-GBM disease patients with a rapidly progressive glomerulonephritis (RPGN). In a confirmatory test setting, the immunoblot had an optimal sensitivity and specificity of 97.4 and 98.1% for PR3-ANCA and 98.5 and 96.4% for MPO-ANCA, respectively. With increasing test result ranges, a higher interval likelihood ratio (LR) was found for both ANCA entities. When evaluating for ANCA in patients with RPGN, the highest diagnostic accuracy (sensitivity 92.9% and specificity 100%) was obtained by using different cut-off values of positivity for PR3- (>5) and MPO-ANCA (>10). Also, the diagnostic performance for detecting anti-GBM was good (sensitivity 100% and specificity 100%). There are advantages over other assays in terms of time, costs, and interpretation of results. The immunoblot is a useful addition to current guidelines, particularly when a rapid diagnosis is necessary.